An experimental investigation on the influence of enhancers fuel and some performance indicators on a two-leg subsoiler plow - Ayoub, Hilal H.; Rajab, Raqeeb H.; Hilal, Yousif Y. (Edelweiss Applied Science and Technology, 2024)
The research was implemented in Al-Hamdaniya District, one of the districts of Nineveh Governorate in northern Iraq, located southeast of Mosul. The soil texture of the field is Clay loam. In the present study, fuel consumption, vibration in the driver’s seat, noise, and exhaust gas temperature were investigated during four types of fuel that include diesel without enhancers fuel, diesel with Power Max enhancers fuel, diesel with Bardahl enhancers fuel, and diesel with Max-Tane enhancers fuel, and two angles of penetration were 45◦ and 55◦. Two plowing depths of 35 and 45 cm were considered. The results indicated that fuel consumption and exhaust gas temperature recorded a significantly negative loss with diesel fuel without improved additives, reflecting the economic loss and the efficiency performance. The results showed the positive superiority of diesel fuel with improved additives in the fuel consumption, vibration in the driver’s seat, noise, and exhaust gas temperature, except diesel with Max-Tane and diesel with Power Max enhancers achieved a negative effect increase in vibration in the driver’s seat and noise, respectively. However, the values remained within the measurements approved by European Parliament Directive 2003/10/EC. Moreover, increasing the angle of penetration and plowing depths increases fuel consumption, vibration in the driver’s seat, noise, and exhaust gas temperature. Finally, the results indicate the superiority of the fuel-improved additives and angle of penetration with plowing depths achieved the best results in the studied trait except for the vibration in the driver’s seat at the intersection diesel with Max-Tane with a penetration angle of 55o and plowing depth of 45 cm.